Diagnostic performance of CT signs for predicting adnexal torsion in women presenting with an adnexal mass and abdominal pain: A case-control study. Issue 98 (January 2018) - Mandoul, Caroline; Verheyden, Cécile; Curros-Doyon, Fernanda; Rathat, Gauthier; Taourel, Patrice; Millet, Ingrid
Highlights: Diagnosing torsion in patients with abdominal pain and adnexal mass is challenging. Adnexal torsion could be diagnosed at computed tomography with high performance. An inter-utero-ovarian mass is an accurate CT finding for diagnosing torsion. Appropriate care can be given to patients based on CT findings. Prompt surgery, mandatory to preserve fertility, can be performed with confidence. Abstract: Purpose: To determine which CT findings or combinations of CT findings could accurately identify adnexal torsion in a cohort of women admitted for abdominal pain and presenting with an adnexal mass. Materials and methods: The local institutional review board approved this retrospective case-control study involving adults—the informed consent requirement was waived. Enhanced computed tomography (CT) findings of 32 consecutive adnexal torsion and 32 control patients admitted for abdominal pain and presenting with an adnexal mass were independently reviewed by two radiologists, with consensus by a third one, for all CT findings commonly assessed in adnexal torsion. All twisted and untwisted adnexa were confirmed by surgery. Univariate and multivariate analyses were performed for adnexal torsion prediction. Results: The median patient age was 41 years (interquartile range, 30.5–62 years). Only benign masses were encountered in the torsion group. Five CT features were significantly associated with adnexal torsion: a large ovary with a threshold at 80 mm (p = 0.005), median or contralateral displacement of the adnexa (p = 0.00014), asymmetric wall thickening of the mass (p < 0.0001), inter-utero-ovarian mass (p < 0.0001) and whirlpool sign (p = 0.0006). In the multivariate analysis, only the inter-utero-ovarian mass was independently associated with adnexal torsion (odds ratio = 130 (CI95%: 15-infinite), p < 0.0001) with an excellent overall diagnostic performance (AUC = 0.89; CI95%: 0.81–0.97). It was a sensitive (Se = 97%, CI95%: 84–100) and specific feature (Sp = 81%, CI95%: 64–93). Conclusion: An inter-utero-ovarian mass is an accurate and reliable CT finding for diagnosing adnexal torsion in patients with acute abdominal pain and an adnexal mass.